Genetic Diversity and Structure of a Critically Endangered Ornamental Species, Rhododendron farinosum, with Extremely Small Populations - Fengjuan Li; Linyuan Fan; Jingli Zhang; Wen Liu; Wei Li; Yongpeng Ma; Hong Ma (Horticulturae)
A comprehensive study of the genetic characteristics of endangered species is a prerequisite for their effective conservation and management. Rhododendron farinosum is an endangered ornamental species with extremely small populations located in northeastern Yunnan Province. To unravel the reasons behind the endangerment of this species and provide guidance for the rational conservation of this species, this study obtained a large number of SNP loci by using double-digest restriction-site-associated DNA sequencing (ddRAD-seq) to evaluate the genetic diversity and genetic structure of R. farinosum, as well as to infer the population history of this species. Our findings reveal that, at the population level, R. farinosum exhibited a high genetic diversity (π = 0.1948 ± 0.0020, HE = 0.1880 ± 0.0020). The FST values (0.1383–0.2231) indicated high genetic differentiation among the three populations. The AMOVA revealed that 62.83% of the genetic variation originated within populations and 37.17% between populations. The PCA, Structure, and UPGMA consistently depicted that the three populations of R. farinosum are clearly distinguished into three clusters. Furthermore, the effective population size of R. farinosum was inferred to date back to 95,000 years ago using the stairway plot, with a continuous decline from 3292 years. Based on these findings, we propose conservation strategies and management measures for R. farinosum.